2006
DOI: 10.1074/jbc.m607128200
|View full text |Cite
|
Sign up to set email alerts
|

A Multienzyme Network Functions in Intestinal Protein Digestion by a Platyhelminth Parasite

Abstract: Proteases frequently function not only as individual enzymes but also in cascades or networks. A notable evolutionary switch occurred in one such protease network that is involved in protein digestion in the intestine. In vertebrates, this is largely the work of trypsin family serine proteases, whereas in invertebrates, cysteine proteases of the papain family and aspartic proteases assume the role. Utilizing a combination of protease class-specific inhibitors and RNA interference, we deconvoluted such a networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
205
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(225 citation statements)
references
References 62 publications
(68 reference statements)
13
205
0
3
Order By: Relevance
“…First, SmCD 1.2 kb-dsRNA was employed for treatment of 3-hour-old schistosomules that were cultured for the next 14 days. dsRNA of this length was employed because earlier studies with cathepsin B1 of S. mansoni had shown that dsRNA of at least one kb in length induced strong knockdown and phenotypic effects against a proteolytic enzyme, which like cathepsin D, is gut-localized and participates in hemoglobin proteolysis [6,18]. Second, a SmCD dsRNA of 0.5 kb in length was prepared for use with seven, nine and 11 day old somules that were cultured for seven days after dsRNA treatment.…”
Section: Schistosomules Treated With Cathepsin D Dsrna Show Retardedmentioning
confidence: 99%
See 4 more Smart Citations
“…First, SmCD 1.2 kb-dsRNA was employed for treatment of 3-hour-old schistosomules that were cultured for the next 14 days. dsRNA of this length was employed because earlier studies with cathepsin B1 of S. mansoni had shown that dsRNA of at least one kb in length induced strong knockdown and phenotypic effects against a proteolytic enzyme, which like cathepsin D, is gut-localized and participates in hemoglobin proteolysis [6,18]. Second, a SmCD dsRNA of 0.5 kb in length was prepared for use with seven, nine and 11 day old somules that were cultured for seven days after dsRNA treatment.…”
Section: Schistosomules Treated With Cathepsin D Dsrna Show Retardedmentioning
confidence: 99%
“…Second, a SmCD dsRNA of 0.5 kb in length was prepared for use with seven, nine and 11 day old somules that were cultured for seven days after dsRNA treatment. We tested the shorter dsRNA probe because it had become apparent that shorter dsRNAs of 300 to 700 bp, and indeed very short 21 bp short interfering RNAs (siRNAs), triggered profound gene suppression of gut-associated proteases of S. mansoni [6,15], and because there exists the possibility that residual dsRNAs might interfere with downstream analysis of gene-silenced cells, specifically by serving as spurious templates in RT-PCRs employed to investigate levels of target gene transcripts [24].…”
Section: Schistosomules Treated With Cathepsin D Dsrna Show Retardedmentioning
confidence: 99%
See 3 more Smart Citations